Retracted: Pharmaceutical Reagent Inventory Strategy Based on Contract Shelf Life and Patient Demand - Imaging, Contrast Media & Molecular (Contrast media and molecular imaging, 2023)
[This retracts the article DOI: 10.1155/2022/5046141.].[This retracts the article DOI: 10.1155/2022/5046141.].